10.9k views
0 votes
Confirm that f and g are inverses by showing that f(g(x)) = x and g(f(x)) = x? f(x)=(x-7)/(x+2) and g(x)=(-2x-7)/(x-1)

2 Answers

4 votes

Answer:

Explanation:

f(g(x))=f(-2x-7/x-1)

=((-22-7)/(x-1) -7 )/ ((-22-7)/(x-1) +2 )

=(-22-7-7(x-1)/x-1) /(-22-7+7(x-1)/x-1)

=-gx/-g = x

g(f(x))= g(x-7/x+2)

=-2(x-7/x+2)-7/(x-7/x+2)-1

=(-2(x-7)-7(x+2)/x+2)/ x-7-(x+2)/x+2

=-gx/-g =x

User Novy
by
5.6k points
3 votes
hello here is a solution : 
Confirm that f and g are inverses by showing that f(g(x)) = x and g(f(x)) = x? f(x-example-1
User Michaldo
by
6.3k points